Pengaruh Rekrutmen, Pelatihan, dan Penempatan Tenaga Ahli terhadap Capacity Building Dewan Perwakilan Rakyat Daerah Kota Palembang - Wenny Yudi Puranti; Fakhry Zamzam; Harsi Romli (Program Magister Manajemen Indo Global Mandiri University, 2020)
The research purpose was specifically to analyze and assess the effect of recruitment, training, and placement of experts on the capacity building of regional representatives council partially and simultaneously. The research method used an associative survey approach, the collection of field data used questionnaires and interviews,analyzing data used quantitative techniques (tools, spss 23). The research population was 114 DPRD secretariat employees with 60 employees as the sample. The t-test results implied that partially recruitment affected on capacity building with t count 2.511 > t table 2.003, while partially training had a positive and not significant effect with t count 0.200 < t table 2.003, and partially placement had a negative and not significant effect on capacity building. The results of the F test revealed that simultaneously recruitment, training,and placement had a positive and significant effect on capacity building with F count 2.809 > F table 2.76.